Flatlands fly to third dimension. - Flusfeder, Helena (Times Higher Education Supplement, 1997)
Reports on the Technion-Israel researchers' development of a fast software which turns flat-looking satellite pictures into landscapes with a three-dimensional realistic look. Technique used to create the three-dimensional image.